2013
DOI: 10.3109/09273948.2013.841957
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Corneal Biomechanical Properties in Patients with Rheumatoid Arthritis: A Study by Ocular Response Analyzer

Abstract: RA patients had lower CH and CRF, but higher IOPcc values than healthy controls. RA should be considered when the corneal biomechanical properties measured by the ORA are used for diagnoses or therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 27 publications
0
8
1
Order By: Relevance
“…These findings are unlikely to those previous studies reported by Prata et al, Tas et al and Can et al found RA patients have higher IOPcc measurements when compared to control group. 10,11,13 There may be an association between autoimmunity and glaucoma but we did not find increased IOP in RA patients in our study. Large groups are necessary to evaluate whether RA patients have higher IOP measurements according to their age with considering their systemic therapy.…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations
“…These findings are unlikely to those previous studies reported by Prata et al, Tas et al and Can et al found RA patients have higher IOPcc measurements when compared to control group. 10,11,13 There may be an association between autoimmunity and glaucoma but we did not find increased IOP in RA patients in our study. Large groups are necessary to evaluate whether RA patients have higher IOP measurements according to their age with considering their systemic therapy.…”
Section: Discussioncontrasting
confidence: 45%
“…A more comprehensive study has been reported by Tas et al with 39 patients with RA in which duration of disease was not mentioned. 11 They also found lower CH and CRF and higher IOPcc values than control group. In their study 2 of the patients had a history of corneal involvement and 5 had episcleritis.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Taş et al 22 reported lower CH and CRF values in patients with rheumatoid arthritis compared with age-matched controls, and the authors found higher IOPg and IOPcc values compared with the control group. Taş et al 22 reported lower CH and CRF values in patients with rheumatoid arthritis compared with age-matched controls, and the authors found higher IOPg and IOPcc values compared with the control group.…”
Section: Discussionmentioning
confidence: 96%